Legal Consequences for Cancellation of a Willing Deed in the Settlement of Instruction Disputes - Muhammad Ihsan Kurniawan; Anshori Anshori (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
This research is about understanding grants, testament grant deeds and how to cancel a testament grant deed as well as analyzing the factors that cause a testament grant deed containing a grant (legaat) to be canceled by the court and the legal consequences of the object of the testament grant. The research was conducted using a normative juridical legal research method and then described descriptively. The results of the study can be concluded. the factors that cause the will (legaat) grant deed can be canceled and the legal consequences after the testament grant deed are canceled through a decision that has permanent legal force (inckracht). Inherited assets often cause various legal and social problems, therefore they require arrangement and settlement in an orderly and orderly manner in accordance with applicable laws and regulations. Making a will (testament) is a legal act, a person determines what happens to his wealth after death. The creation of a testament is bound by a certain form and method if it is ignored it can cause the testament to be canceled. In accordance with the provisions of Article 875 of the Civil Code that a will made before a notary can be canceled if it turns out that the procedure for making it is not carried out in accordance with the terms and conditions that apply to the will grant deed.